Human genetics and didactic transposition: the expression of skin color, eye color, and height in Brazilian and Portuguese textbooks - Franzolin, Fernanda (2017)
The knowledge produced by genetic science is constantly expanding. However, the “taught knowledge” is not just a simplification of the knowledge produced by science, since it is also a result of values and practices. The objective of this study is to analyze how some examples of the expression of human characteristics in school textbooks approximate or deviate from reference knowledge found in literature. Secondary school textbooks were analyzed: six Brazilian collections and three Portuguese collections. Three topics were analyzed (skin color, eye color and height) and data were compared to scientific reference literature concerning these topics, which was composed of recent scientific papers and teacher training reference books. This analysis used the methodology developed in previous studies by Franzolin (2012) on “categories of types” and “categories of implications” and the KVP model (Clément, 2006). This study shows that most textbooks are close to the reference literature in mentioning the polygenic determination of the analyzed characteristics (skin color, eye color and height) and the influence of the environment in the expression of these characteristics. Textbooks which deviate from reference literature may cause barriers to the central content understanding. In the Portuguese context, it was evident that the practice of adopting new topics in the curriculum lead to the elimination of such information, not valued in official curriculum documents.